2018
DOI: 10.3233/cbm-170550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of breast cancer hub genes and analysis of prognostic values using integrated bioinformatics analysis

Abstract: Fifteen genes were selected as hub genes because of high degrees, among which, low expression of four genes was associated with worse OS of patients with BC, including RPS9, RPL11, RPS14 and RPL10A. Additionally, the small molecular agent emetine may be a potential drug for BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…In current, some relevant studies based on the database were published regarding hub genes in breast cancer. For instance, Fang et al identified 15 genes from one GEO datasets by bioinformatic approach including the raw data analysis of GSE10797, GO and KEGG pathway enrichment, PPI network construction and module analysis, survival analysis of hub genes, and Connectivity Map (cMap) database analysis (Fang and Zhang, 2017). Tang et al identified 10 hub genes in brain metastasis breast cancer from two GEO databases, and four hub gene expression of which were closely associated with the OS of breast cancer patients by developing an integrated method including GO and KEGG pathway enrichment analysis, PPI network analysis, hub gene identification, transcription factor (TF) analyses, and OS analysis (Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In current, some relevant studies based on the database were published regarding hub genes in breast cancer. For instance, Fang et al identified 15 genes from one GEO datasets by bioinformatic approach including the raw data analysis of GSE10797, GO and KEGG pathway enrichment, PPI network construction and module analysis, survival analysis of hub genes, and Connectivity Map (cMap) database analysis (Fang and Zhang, 2017). Tang et al identified 10 hub genes in brain metastasis breast cancer from two GEO databases, and four hub gene expression of which were closely associated with the OS of breast cancer patients by developing an integrated method including GO and KEGG pathway enrichment analysis, PPI network analysis, hub gene identification, transcription factor (TF) analyses, and OS analysis (Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins, immune cells, vessels, and mural cells can become dysregulated during the progression of LSCC. Identification of these markers may provide value as prognostic tools (Fang & Zhang, 2017) and druggable targets (Finan et al, 2017). For example, Meng et al (2019) has identified differences in the immune microenvironment between LSCC and non-squamous NSCLCs and demonstrated the influence on patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The dysfunction of ECM-receptor interaction may lead to the abnormal activation of signal transduction pathways, including Ras/ Raf/MAPK, Raf/JNK, Rho/RAC/Pak and PI3K/Akt/mTOR. So as to create a tumor microenvironment that can promote tumor survival, angiogenesis and invasion 29 . PI3K-Akt signaling pathway is the most common dysregulated pathway in many tumor cells.…”
Section: Discussionmentioning
confidence: 99%